Os marcadores discursivos, pronomes e verbos e seus efeitos de sentido em editoriais das revistas Carta Capital e Veja sob uma análise linguística - Cruz, Lucas Saldanha da (2018)
As a result of the Brazilian political crisis, especially since 2015, we intend to analyze discourses related to this issue. We opted for editorials, as they present the opinions of the media. In addition, we have selected the magazines Veja and Carta Capital because they are representative of the mainstream media and, supposedly, can present opposing speeches. Thus, this dissertation aims to reflect on the enunciative-discursive sense effects of discursive markers, pronouns and verbs that could contribute to the identification of argumentative tendencies in the editorials of the two journals. The theoretical basis is composed of Enunciation Linguistics studies, basically, from Benveniste (1989, 1991), Flores and Teixeira (2013) and Flores (2013). The corpus for analysis consists of 82 editorials of the magazines Carta Capital e Veja on the theme: Brazilian political crisis. The collection period was January 1, 2015, the date of the inauguration of President Dilma, until May 31, 2016, the month in which the president's impeachment process intensified. With regard to quantitative questions, we identified the occurrences of discursive markers, pronouns and verbs in the corpus for later qualitative analysis. Qualitatively, we reflect on the effects of meaning arising from the use of these markers, pronouns and verbs in linguistic materiality contributing to the enunciative-discursive sense effects. As results, we can conclude that these grammatical categories contribute to the identification of the argumentative tendency from its effects of sense. We can see that in Carta Capital editorials emerges an imaginative and empathetic subject, with a language style quite peculiar to an editorial. In Veja, we observe that a professorial subject emerges, with a methodical tone. Through this dissertation, we can prove that the two journals have divergent opinions on Brazilian political issues. In addition, we consider, from all the work, of utmost importance if we work in the classroom the editorial genre and the grammatical categories from an enunciative bias